PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. LAUTAN TEDUH DI KOTA METRO - Suwarto, Suwarto (Derivatif : Jurnal Manajemen, 2019)
The results of this study concluded that the results obtained from Organizational Culture and Leadership Style on Employee Performance at PT. Metro Sea Ocean City is based on the calculation of multiple linear regression tests that the X1 variable (Organizational Culture) and X2 (Leadership Style) have a significant influence on employee performance. The existence of a positive relationship between the variables of Organizational Culture (X1) and X2 (Leadership Style) on the variable Y (Employee Performance) means that the variable X1 (Organizational Culture) and X2 (Leadership Style) has increased Y variable (Employee Performance). Vice versa, if the free variable is decreased, it will be followed degandecline, it will be followed by a decrease in the dependent variable. Variable X1 (Organizational Culture) and X2 (Leadership Style) have a relationship with the variable Y (Employee Performance). Â Keywords: Organizational Culture and Leadership Style, Employee Performance